Children's inter-age relations in rural schools - Paulina De la Fuente-García; Carmen Alvarez (Universidade Federal do Norte do Tocantins, 2024)
The aim of this research is to analyse children's inter-age relationships in rural schools, given that the low number of pupils can limit the possibilities of socialising with children of the same age, encouraging relationships with older or younger classmates, both in the classroom and in the playgrounds. The research carried out was a mixed research, using a questionnaire sent to rural schools all over the country, and ethnographic fieldwork during four months in a rural school. The results show the good inter-age relationships that are generated in these environments and the good influence that multi-grade education has on the education and integral development of children. The study concludes by highlighting the value of children's inter-age relationships in rural schools and calling for further studies to increase knowledge on the subject.